Density functional investigations of electronics structure and dehydrogenation reactions of Al- and Si-substituted magnesium hydride - Kelkar, Tuhina; Pal, Sourav; Kanhere, Dilip G. (ChemPhysChem, 2008)
{The effect on the hydrogen storage attributes of magnesium hydride (MgH2) of the substitution of Mg by varying fractions of Al and Si is investigated by an ab initio plane-wave pseuodopotential method based on density functional theory. Three supercells, namely, 2 x 2 x x 3 x 1 x 1 and 5 x 1 x 1 are used for generating configurations with varying amounts (fractions x=0.0625, 0.1, and 0.167) of impurities. The analyses of band structure and density of states (DOS) show that, when a Mg atom is replaced by Al, the band gap vanishes as the extra electron occupies the conduction band minimum. In the case of Si-substitution, additional states are generated within the band gap of pure MgH2-significontly reducing the gap in the process. The reduced band gaps cause the Mg-H bond to become more susceptible to dissociation. For all the fractions, the calculated reaction energies for the stepwise removal of H-2 molecules from Al- and Si-substituted MgH2 ore much lower than for H-2 removal from pure MgH2. The reduced stability is also reflected in the comparatively smaller heats of formation (Delta H-f) of the substituted MgH2 systems. Si causes greater destabilization of MgH2 than Al for each x. For fractions x = 0.167 of Al
Keywords: band structure; Density functional calculations; hydrides; Hydrogen storage; Thermodynamics